Flexible and Transparent Nanocomposite of Reduced Graphene Oxide and P(VDF-TrFE) Copolymer for High Thermal Responsivity in a Field-Effect Transistor - Tran Quang Trung; Ramasundaram, Subramanian; Hong, Seok Won; Lee, Nae-Eung (WILEY-V C H VERLAG GMBH, 2014)
A new class of temperature-sensing materials is demonstrated along with their integration into transparent and flexible field-effect transistor (FET) temperature sensors with high thermal responsivity, stability, and reproducibility. The novelty of this particular type of temperature sensor is the incorporation of an R-GO/P(VDF-TrFE) nanocomposite channel as a sensing layer that is highly responsive to temperature, and is optically transparent and mechanically flexible. Furthermore, the nanocomposite sensing layer is easily coated onto flexible substrates for the fabrication of transparent and flexible FETs using a simple spin-coating method. The transparent and flexible nanocomposite FETs are capable of detecting an extremely small temperature change as small as 0.1 degrees C and are highly responsive to human body temperature. Temperature responsivity and optical transmittance of transparent nanocomposite FETs were adjustable and tuneable by changing the thickness and R-GO concentration of the nanocomposite.